2020
DOI: 10.1371/journal.pone.0228727
|View full text |Cite
|
Sign up to set email alerts
|

Cell-free hemoglobin increases inflammation, lung apoptosis, and microvascular permeability in murine polymicrobial sepsis

Abstract: Increased endothelial permeability is central to the pathogenesis of sepsis and leads to organ dysfunction and death but the endogenous mechanisms that drive increased endothelial permeability are not completely understood. We previously reported that cell-free hemoglobin (CFH), elevated in 80% of patients with sepsis, increases lung microvascular permeability in an ex vivo human lung model and cultured endothelial cells. In this study, we augmented a murine model of polymicrobial sepsis with elevated circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Among them, excess of free heme is a potential offending agent as it has been shown to exacerbate and contribute to the pathogenesis of numerous in ammatory diseases [2]. Therefore, it may be postulated that accumulated free heme and Hb could be involved in the mechanisms mediating pulmonary permeability and in ammation in COVID-19 patients [3]. Protective mechanisms against free heme include HO-effector molecules biliverdin/bilirubin, CO and ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, excess of free heme is a potential offending agent as it has been shown to exacerbate and contribute to the pathogenesis of numerous in ammatory diseases [2]. Therefore, it may be postulated that accumulated free heme and Hb could be involved in the mechanisms mediating pulmonary permeability and in ammation in COVID-19 patients [3]. Protective mechanisms against free heme include HO-effector molecules biliverdin/bilirubin, CO and ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…SIRS caused by gram-negative bacteria is known to be a host response to lipopolysaccharide [ 18 , 19 ] and accompanied by increased production of inflammatory mediators such as NO, IL-1, IL-6, and TNF-α resulting in vascular leakage and multiple organ dysfunction syndrome (MODS) [ 20 , 21 ]. Increased endothelial permeability is central to SIRS, leading to MODS and death [ 22 , 23 , 24 , 25 ]. Indeed, in addition to the cytopathic role in host defense and innate immune functions, NO plays a major role in vasodilation in SIRS [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using radiolabeled liposomes, we further demonstrated that free heme causes vascular permeabilization resulting in edema [ 28 ]. Accumulated free heme and Hb may thus act as pathophysiologic mechanisms mediating pulmonary permeability and inflammation [ 31 , 32 ]. Alveolar fluid clearance is hampered in ARDS and also likely in hospitalized COVID-19 patients.…”
Section: Can Injury-derived Free Heme Contribute To Covid-19 Pathomentioning
confidence: 99%